Effect of maternal dietary manipulation and in ovo injection of nutrients on the body weight gain, feed conversion ratio, development of lymphoid and digestive organs of turkey poults - BHATTACHARYYA, AMITAV; MAJUMDAR, SAMIR; BHANJA, SUBRAT KUMAR; MANDAL, ASIT BARAN; KADAM, MUKUND M (The Indian Journal of Animal Sciences, 2017)
An experiment was undertaken involving maternal dietary manipulation (NRC 1994-diet A or higher plane of nutrition-diet B), in ovo nutrient injection (in ovo essential amino acids- INA; linolenic acid, linoleic acid, retinol and DL-alpha-tocopherol-INFV; in ovo essential amino acids, linolenic acid, linoleic acid, retinol and DL-alphatocopherol- INAFV, sham control-S and un injected control-C) in a 2 × 4 factorial design. Turkey breeder hens (200) and viable toms (24) of 30 to 35 weeks of age of small white variety were distributed into 2 treatment groups comprising 4 replicates of 25 hens and 3 toms in each treatment. First 4 replicates were offered diet A and the other 4 replicates were maintained on a higher plane of nutrition (diet B) for 8 weeks. Fertile eggs (548) were collected and on 21st embryonic day (ED), the eggs were in ovo injected with nutrients. In ovo nutrient injected chicks had significantly better FCR compared to the control group and INA treatment poults had significantly better FCR compared to the other treatment groups throughout the experiment. Small intestine length was significantly lower in the INAFV treatment group compared to the other treatment groups. Caecal length was significantly lower in the INA treatment group compared to the un-injected control group and the INFV group. Hence, it may be concluded that in ovo injection of nutrients may have a positive effect in production indices of turkey poults.